SECULAR TRENDS OF NUTRITIONAL STATUS OF ADOLESCENTS IN PITIMBÚ, SOUTH COAST OF PARAÍBA (BRAZIL): TRANSITION OF 2004 TO 2007 (Fiep Bulletin - online, 2014)
The objective of this study was to analyze the temporary tendency of nutritional disturbances in adolescents of municipal district of Pitimbú (PB) during 2004 to 2007. Material and methods: They announced 1093 adolescents in the age group from 10 to 17 years of both sexes. The instruments for collection of data were: balances digital Camry and estadiometer model Personal Sanny to measure the body mass (BM) and stature (STA), respectively. The nutritional status was set out through the Body Mass Index (BMI) and adopted the percentis (P) of CDC (2000) and the classification of WHO (1995): 85=excess. The analysis of the data used SPSS version 13.0. Results: During 2004-2007 there were not significant changes (p>0,05) in the averages of BM, STA and BMI. In spite of, of the point of view of the nutritional tendency, it was observed in the masculine that BM increased between 2004 and 2007; was not the boys' STA altered in the same time and BMI presented a sensitive elevation among 2004 to 2007 in both sexes (? of 17,8kg/m2 for 18,0 kg/m2; ? of 18,8kg/m2 for 19,1 kg/m2). In the feminine, there was increase in the averages of BM of 2006 and 2007; when analyzed STA the maintenance of the same from 2004 to 2006 was observed with increase in 2007; IMC showed oscillation with tendency to the gradual increase. When seen in both sexes and stratified by age group was detected significantly between 10 and 14 years in boys values lower to feminine (p
Keywords: Nutrition transition; Teen Health; Obesity